Peningkatan Literasi Numerik melalui Pengenalan Aplikasi Perhitungan Bilangan Prima, Ganjil, dan Genap di Kalangan Pelajar SMK Bina Sriwijaya Palembang menggunakan Microsoft Visual Basic 6.0 - Munawaroh, Faridatul; Aqil, Ibnu; Triana, Dora Indah; Sulastri, Asiawatie (Journal of Social and Community Service, 2025)
The development of information technology provides an opportunity to create innovation in the world of education, especially in supporting the calculation process that is often carried out by teachers, students, and education personnel. One solution that can be implemented is the development of the "Smart Calculator" application based on Visual Basic 6.0. This application is designed to provide special features that can help calculate average values, simple statistical data analysis, and automatic value conversion. This community service activity aims to implement the Smart Calculator application as a practical and efficient tool in improving the quality of the learning process and education management. The methods used include user needs analysis, software development, application usage training for teachers and students, and evaluation of the effectiveness of the application in an educational environment. The results of the activity show that the Smart Calculator application provides significant benefits in facilitating administrative work and supporting the teaching and learning process. With a simple and user-friendly interface design, this application has succeeded in increasing calculation efficiency by up to 50% compared to manual methods. Through this activity, it is hoped that the Smart Calculator application can be widely adopted as an innovative solution in supporting the world of education.